Benefit of co-curricular - Abu Bakar, M.L.A.H.; Esa, A. (Elixir All rights reserved, 2017)
Service learning is a method of teaching where students apply their academic skills and knowledge to address real-life needs in their own communities. Service learning is a pedagogical strategy that facilitates a student's growth in academics, social maturity, critical thinking, and communication, collaboration, and leadership skills. This educational opportunity possesses enormous potential to move higher education in the direction of civic involvement by taking the classroom into the community. Student experienced stronger positive effects on critical thinking, degree plans, sense of control over their own academic success, and preference for higher-order cognitive tasks.